Factors Affecting the Efficiency of Pipe Pumped Concrete for Multi-Story Buildings - Neha Deshmukh, Harsha Abhichandani, Abhay Shelar, Amruta Chavan (Mathematical Statistician and Engineering Applications, 2022)
Concrete has been crucial Within the endeavors of planners and engineers who sought out reliable and affordable materials for concrete and high-rise structures. Whether ordinary or RMC, concrete for building of small-height (up to three to five stories) is moved and utilized to move concrete using buckets, wheelbarrows, culverts, and occasionally cranes. It is time consuming to place the concrete in the bucket,crane,etc method since it is not an endless procedure and can impact the concrete productivity as the structure rises and gets better. In this situation, pumping is a practical way to pump concrete. The productivity improvement is just one of several positive features of the concrete pump. Increased productivity is crucial since it results in quicker completion, which enables the owner to return on his investment rapidly. To replace concreting buildings, the variables affecting the productivity and efficiency of pumped concrete resources are explored. Information about the pumped concrete for this study, factors affecting concrete productivity in a high-rise building, and the need for concrete pumps. In the study, additional variables that affect concrete placement will be taken into account and offer many advantages like increase in productivity. The pump offers great performance in areas where humans cannot reach easily.